Kebebasan Terikat: Telaah 1 Korintus 6:12-20 Dasar Gereja Merespons Friends With Benefits Pada Generasi Z - Kewo, Verny; Labobar, Jerson (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2026)
The behavior of friends with benefits is an act of sexual immorality that damages the body as the temple of God and the fellowship of the church. FWB behavior often occurs among Gen Z, and this act greatly pollutes human relationships with God and fellow human beings. Using descriptive qualitative research methods and a theological examination of 1 Corinthians 6:12-20 to critique sexual misconduct that is not only committed by the Corinthian congregation but also by Gen Z through non-committal relationships or FWB. Therefore, this study not only explores the message and meaning of the text but also serves as a reference for the church in responding to FWB relationships that are prevalent among Gen Z. The church must respond appropriately because FWB relationships can damage the lives of individuals and the church. Through this phenomenon, the church should not only voice prohibitions but also restore. Therefore, through this study, the biblical text becomes a reference for the church in criticizing such behavior.